Anticoagulants in Pediatric Sinovenous Thrombosis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2010)
Safety and outcome of anticoagulant therapy in neonates and children with cerebral sinovenous thrombosis (CSVT) were determined in a study at the Hospital for Sick Children and Toronto Western Hospital, Ontario, Canada.